2017
DOI: 10.1080/14767058.2017.1407309
|View full text |Cite
|
Sign up to set email alerts
|

The influence of a diet based on flaxseed, an omega-3 source, during different developmental periods, on the blood pressure of rats submitted to stress

Abstract: Results suggest a possible factor from a flaxseed diet against the effects of stress on a blood pressure in all periods of life but especially in the gestation and lactation periods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In a recent study, we demonstrated that anxiety- and depressive-related behaviors as well as neuronal atrophy in the medial PFC observed in mice fed with a diet deficient in ω3 PUFAs are both mediated by HPA axis hyperactivity ( Larrieu et al, 2014 ). ω3 PUFAs supplementation beyond weaning prevents chronic stress-induced increases in plasma corticosterone levels ( Ferraz et al, 2011 ; Larrieu et al, 2014 ; Meneses et al, 2017 ), PFC neuronal shrinkage ( Larrieu et al, 2014 ) as well as anxiety- and depressive-like behaviors ( Ferraz et al, 2011 ; Larrieu et al, 2014 ). In another study, we confirmed and followed up on their initial observations by demonstrating that GR signaling pathway is compromised in the PFC of ω3 PUFA-deficient mice along with dendritic arborization atrophy ( Larrieu et al, 2015 ).…”
Section: Relevant Mechanisms For Nutritional ω3 Pufa-induced Mood-relmentioning
confidence: 99%
“…In a recent study, we demonstrated that anxiety- and depressive-related behaviors as well as neuronal atrophy in the medial PFC observed in mice fed with a diet deficient in ω3 PUFAs are both mediated by HPA axis hyperactivity ( Larrieu et al, 2014 ). ω3 PUFAs supplementation beyond weaning prevents chronic stress-induced increases in plasma corticosterone levels ( Ferraz et al, 2011 ; Larrieu et al, 2014 ; Meneses et al, 2017 ), PFC neuronal shrinkage ( Larrieu et al, 2014 ) as well as anxiety- and depressive-like behaviors ( Ferraz et al, 2011 ; Larrieu et al, 2014 ). In another study, we confirmed and followed up on their initial observations by demonstrating that GR signaling pathway is compromised in the PFC of ω3 PUFA-deficient mice along with dendritic arborization atrophy ( Larrieu et al, 2015 ).…”
Section: Relevant Mechanisms For Nutritional ω3 Pufa-induced Mood-relmentioning
confidence: 99%
“…The intake of a high-fat diet added with flaxseed flour during pregnancy and lactation did not lead to changes in systolic blood pressure in male offspring of diabetic rats at 100 days of life, 34 corroborating our results; however, another study reported that the intake of flaxseed flour during pregnancy and lactation led to a blood pressure decrease in the offspring of healthy rat dams. 35 In addition, our study showed that exercise training did not lead to differences in blood pressure between sedentary and trained animals. Studies with sedentary animals and trained animals also presented similar blood pressure levels between groups, [36][37][38] yet another study showed that chronic exercise training (treadmill) led to a decrease in blood pressure in normotensive rats.…”
Section: Discussionmentioning
confidence: 51%